Across-species benefits of adrenalectomy on congenital generalized lipoatrophic diabetes: a review - Contreras, Patricio H.; Vigil, Pilar (Frontiers in Endocrinology, 2024)
Two adrenalectomies performed fourteen years apart notoriously alleviated insulin resistance in a female teenager with Congenital Generalized Lipoatrophy (CGL, 1988) and in a murine model of CGL (2002). Following a successful therapeutic trial with anti-glucocorticoids, we performed the first surgical procedure on an 18-year-old girl. Before surgery, the anti-glucocorticoid therapy produced a rapid and striking drop in fasting serum insulin levels (from over 400 to 7.0 mU/L) and a slower -but impressive-fall in fasting serum triglycerides from 7,400 to 220-230 mg/dL. In contrast, fasting serum glucose levels dropped more slowly, from 225-290 to 121-138 mg/dL. Two weeks following total adrenalectomy, the fasting serum glucose level was 98 mg/dL, with a corresponding serum insulin level of 10 mU/L. During an Oral Glucose Tolerance Test, the 2-hour serum glucose was 210 mg/dL, and serum insulin values during the test did not exceed 53 mU/L.In 2002, the A-ZIP/F1 hypoleptinemic mouse had its adrenal glands removed. Even though this CGL model does not respond well to leptin replacement, an infusion of recombinant leptin reduced the characteristic hypercorticosteronemia of this murine model of CGL. Adrenalectomy in this transgenic mouse improved insulin sensitivity in the liver and muscle.In summary, adrenalectomy -in both a human and a mouse case of CGL-limited adipose tissue exposure to corticosteroid action and led to a notorious metabolic improvement. On a broader scenario, given that leptin restrains the adrenal axis, the reduced leptin activity of the leptin resistance displayed by obese subjects should lead to adrenal axis overactivity. This overactivity should result in elevated serum levels of free cortisol, free fatty acids, and glycerol. In this manner, leptin resistance should lead to peripheral (adipose tissue, liver, and muscle) insulin resistance and islet beta-cell apoptosis, paving the way to Type 2 diabetes.